Peran Ganda Perempuan: Sebuah Analisis Filosofis Kritis - Supartiningsih, Supartiningsih (Jurnal Filsafat "WISDOM", 2003)
The discourse of women in Indonesia brings a wind of change for the empowerment of Indonesian women. The concept of women dual-roles which has been offered, gives inspirations to women movements for reaching equal rights between men and women. This concept, however, is not immune from critics. One of the weekness is: this concept couses the dichotomic mentality appears. The gool of this writing is to analyze critically the concept of women dual-roles. Analysis is done by explaining the strengthness and the weekness of this concept. So, it will be understood comperhensively. The goal of this writing is giving alternative concept that also accomodates the whole of humanity.The wowen discourses based on dichotomy bertween public and domestic area have many probelms. Diametral distinction bertween both tends to appear split personality of women when thet have to fulfill need of self-actualitation. So, it has to be formed new paradigm to solve this dichotomic probelm. Both area should be understood as two points that be related in continum line. So dichotomic probelm can be overcome.Men and women are not contrary, but partnership. The relation between both is partner relationship, not relation of oppressing or dominating each other. Both is a self, although they have different body. Both make complete and immanent each other, so that the responsible capacity, maturity of attitude, and happiness can be reached. It gives that women movements need to give attention of the whole humanity i their struggle for women dignity.